Relationship of Absolute and Relative Lower-Body Strength to Predictors of Athletic Performance in Collegiate Women Soccer Players - Emily Andersen; Robert G. Lockie; J. Jay Dawes (MDPI AG, 2018)
The purpose of this study was to investigate the relationships between absolute and relative lower-body strength on predictors of athletic performance among Division II collegiate women’s soccer players. Archived pre-season testing data for seventeen (n = 17) female National Collegiate Athletics Association (NCAA) Division II soccer players were analyzed, including: vertical jump, 3RM back squat, 505-agility, modified T-test, 10 m and 30 m sprint, and 20 m multistage fitness test (20 m MSFT). Relative strength was calculated based on the estimated 1RM back squat divided by the athlete’s body mass. Significant correlations were discovered between absolute lower-body strength and 505-agility (Right: r = −0.51, p < 0.05; Left: r = −0.59, p < 0.05), modified T-test (r = −0.55, p < 0.05), 10 m and 30 m (r = −0.59, p < 0.05; r = −0.54, p < 0.05), and sprint performance. Relative lower-body strength showed significant correlations with vertical jump (r = 0.54, p < 0.05), 505-agility (Right: r = −0.58, p < 0.05; Left: r = −0.67, p < 0.01), modified T-test (r = −0.75, p < 0.01), 10 m and 30 m (r = −0.59 p < 0.05; r = −0.67, p < 0.01), and the 20 m MSFT (r = 0.58, p < 0.05). These results indicate that strength and conditioning coaches should emphasize the development of absolute and relative lower-body strength with their players to improve power, agility, and speed performance.